Law abiding diplomats: Evidence from diplomatic parking tickets in Washington D.C. (2019)
Why people conform to social norms? Answering this question has important implications for economic development and institutional reforms. Posner (2000a, p. 3) argue that law and economics have no compelling answers. In this paper, we investigate the role of social norms in shaping people's law abiding behavior. We analyze foreign diplomats' compliance with local parking laws while they are stationed in Washington D.C. This is a natural setting to investigate people conformity to social norms since diplomatic immunity gives ample leeway to foreign diplomats to out their host countries' laws. Our empirical results are consistent with the recent literature indicating that the extent to which diplomats' fellow citizens in their home countries observe the rule of law signi cantly a ects diplomat's conformity to social norms abroad. We contribute to the literature by highlighting three additional impor- tant factors that explain diplomat's social norm conformity: i) the legal origin of legal system prevailing in diplomats' home countries, ii) their colonial heritage, and iv) the a nity among diplomats' home and host countries|measured using geographical proximity and military alliances with the U.S. .